FOSTERING PSYCHOLOGICAL SAFETY: THE IMPACT OF INCLUSIVE LEADERSHIP IN SCHOOLS ON TEACHER JOB SATISFACTION AND TEAM INNOVATION - Jeroen de Vries; Eva Janssen; Pieter Hendriks (International Journal of Educatio Elementaria and Psychologia, 2026)
Inclusive leadership in schools has gained increasing attention for its potential to foster a positive organizational climate and improve key outcomes, such as teacher job satisfaction and team innovation. Despite growing interest, there is limited empirical research on how inclusive leadership directly impacts these factors in educational settings. This study aims to examine the relationship between inclusive leadership and teacher job satisfaction, as well as the mediating role of psychological safety in enhancing team innovation in schools. A mixed-methods approach was utilized, combining quantitative surveys administered to 300 teachers with qualitative interviews conducted with 20 school leaders. The results revealed that inclusive leadership significantly contributed to higher levels of teacher job satisfaction and psychological safety. Furthermore, psychological safety was found to mediate the relationship between inclusive leadership and team innovation, highlighting its critical role in promoting a collaborative and innovative work environment. The findings suggest that when school leaders demonstrate inclusive behaviors, such as fostering open communication, valuing diverse perspectives, and supporting professional development, it creates a psychologically safe environment where teachers feel valued and motivated to contribute innovative ideas. This study underscores the importance of inclusive leadership in enhancing both teacher well-being and the innovative capacity of school teams.